2012
DOI: 10.1155/2012/260473
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 and IL-22 in Cerebrospinal Fluid and Plasma Are Elevated in Guillain-Barré Syndrome

Abstract: Guillain-Barré syndrome (GBS) is an acute autoimmune-mediated inflammatory demyelinating disease that causes rapidly progressing paralysis and occasionally respiratory failure. We hypothesized that interleukin (IL)-17 and IL-22 are elevated in GBS and participate in the autoimmune inflammatory response of GBS. We used sandwich enzyme-linked immunosorbent assay (ELISA) to measure the IL-17 and IL-22 levels in the CSF, and plasma from 22 GBS patients at the acute phase and 18 healthy controls (HC). The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(60 citation statements)
references
References 34 publications
2
54
0
2
Order By: Relevance
“…The EGR2 or Krox-20 protein is a transcription factor involved in several processes such as immune response, early smooth musclelike cell differentiation, pathogenesis of fibrosis, and myelination in the peripheral nervous system with implications for the inherited peripheral neuropathies (5)(6)(7)(8)(9)(18)(19)(20). Furthermore, recent results have shown that EGR2 is induced by IL-6 and TGF-b and negatively regulates the expression of IL-17 but not IL-2 or IFN-g in effector T cells (20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The EGR2 or Krox-20 protein is a transcription factor involved in several processes such as immune response, early smooth musclelike cell differentiation, pathogenesis of fibrosis, and myelination in the peripheral nervous system with implications for the inherited peripheral neuropathies (5)(6)(7)(8)(9)(18)(19)(20). Furthermore, recent results have shown that EGR2 is induced by IL-6 and TGF-b and negatively regulates the expression of IL-17 but not IL-2 or IFN-g in effector T cells (20).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent results have shown that EGR2 is induced by IL-6 and TGF-b and negatively regulates the expression of IL-17 but not IL-2 or IFN-g in effector T cells (20). The IL-6 and IL-17 are produced by activated Th17 cells, which are significantly increased in GBS patients (5)(6)(7)(8), and IL-17 and IL-22 levels have been implicated in the acute stage of GBS (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In two studies on CIDP, a major role of CD8-positive T cells was found, involving clonal cellular expansion in blood and nerve samples of these patients, linking systemic and local immune alterations [38,51]. Elevated interleukin-17 levels in different body fluids have also been described [19,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%